2021
DOI: 10.1155/2021/6682944
|View full text |Cite
|
Sign up to set email alerts
|

Postintubation Decline in Oxygen Saturation Index Predicts Mortality in COVID-19: A Retrospective Pilot Study

Abstract: Background. Acute respiratory failure from COVID-19 pneumonia is a major cause of death after SARS-COVID-19 infection. We investigated whether PaO2/FiO2, oxygenation index (OI), SpO2/FiO2, and oxygen saturation index (OSI), commonly used to assess the severity of acute respiratory distress syndrome (ARDS), can predict mortality in mechanically ventilated COVID-19 patients. Methods. In this single-centered retrospective pilot study, we enrolled 68 critically ill mechanically ventilated adult patients with confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 41 In another analysis of C-ARDS patients, it was observed that P/F, SpO 2 /FiO 2 , OI-P mean , and OSI-P mean values were associated with hospital mortality on both the third and seventh days after intubation, with the odds ratio being higher on the seventh day compared to the third day. 42 High OI-P mean and OSI-P mean values were found to be correlated with negative outcomes in both C-ARDS and non-C-ARDS patients, reinforcing their significance in clinical assessments. 12 , 13 , 16 , 42 These studies have reaffirmed the value of conventional oxygenation indices as reliable predictors of outcomes for ARDS patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 41 In another analysis of C-ARDS patients, it was observed that P/F, SpO 2 /FiO 2 , OI-P mean , and OSI-P mean values were associated with hospital mortality on both the third and seventh days after intubation, with the odds ratio being higher on the seventh day compared to the third day. 42 High OI-P mean and OSI-P mean values were found to be correlated with negative outcomes in both C-ARDS and non-C-ARDS patients, reinforcing their significance in clinical assessments. 12 , 13 , 16 , 42 These studies have reaffirmed the value of conventional oxygenation indices as reliable predictors of outcomes for ARDS patients.…”
Section: Discussionmentioning
confidence: 64%
“… 42 High OI-P mean and OSI-P mean values were found to be correlated with negative outcomes in both C-ARDS and non-C-ARDS patients, reinforcing their significance in clinical assessments. 12 , 13 , 16 , 42 These studies have reaffirmed the value of conventional oxygenation indices as reliable predictors of outcomes for ARDS patients. Moreover, the new oxygenation indices, OI-ΔP insp , OSI-ΔP insp , and OSI-MP dyn , have demonstrated superior mortality predictive capabilities compared to the traditional indices in C-ARDS patients.…”
Section: Discussionmentioning
confidence: 64%
“…Reduced peripheral oxygen saturation acts as both a risk factor for intubation [205][206][207] and a guide to the timing of assisted ventilation [208,209]. Moreover, after COVID-19 patients have been intubated, further declines in oxygenation continue to be predictive of mortality risk [210], and improvements in saturation readings can act as a guide to the effectiveness of prone ventilation therapy [211]. Indeed, monitoring of peripheral oxygen saturation is useful not only in prognosticating patients with severe COVID-19, but also in patients discharged from hospital to facilitate the early detection of acute deterioration [212].…”
Section: Peripheral Oxygen Saturationmentioning
confidence: 99%